BRG1 Interacts with Nrf2 To Selectively Mediate HO-1 Induction in Response to Oxidative Stress - Zhang, Jianyong (American Society for Microbiology, 2006)
NF-E2-related factor 2 (Nrf2) regulates antioxidant-responsive element-mediated induction of cytoprotective genes in response to oxidative stress. The purpose of this study was to determine the role of BRG1, a catalytic subunit of SWI2/SNF2-like chromatin-remodeling complexes, in Nrf2-mediated gene expression. Small interfering RNA knockdown of BRG1 in SW480 cells selectively decreased inducible expression of the heme oxygenase 1 (HO-1) gene after diethylmaleate treatment but did not affect other Nrf2 target genes, such as the gene encoding NADPH:quinone oxidoreductase 1 (NQO1). Chromatin immunoprecipitation analysis revealed that Nrf2 recruits BRG1 to both HO-1 and NQO1 regulatory regions. However, BRG1 knockdown selectively decreased the recruitment of RNA polymerase II to the HO-1 promoter but not to the NQO1 promoter. HO-1, but not other Nrf2-regulated genes, harbors a sequence of TG repeats capable of forming Z-DNA with BRG1 assistance. Similarly, replacement of the TG repeats with an alternative Z-DNA-forming sequence led to BRG1-mediated activation of HO-1. These results thus demonstrate that BRG1, through the facilitation of Z-DNA formation and subsequent recruitment of RNA polymerase II, is critical in Nrf2-mediated inducible expression of HO-1.